Pareto-efficient climate agreements can always be renegotiation-proof - Geir B. Asheim; Bjart Holtsmark (University of Oslo, Department of Economics, 2008)
Recent contributions show that climate agreements with broad participation can be implemented as weakly renegotiation-proof equilibria in simple models of greenhouse gas abatement where each country has a binary choice between cooperating (i.e., abate emissions) or defecting (no abatement). Here we show that this result carries over to a model where countries have a continuum of emission choices. Indeed, a Pareto-efficient climate agreement can always be implemented as a weakly renegotiation-proof equilibrium, for a sufficiently high discount factor. This means that one need not trade-off a 'narrow but deep' treaty with a 'broad but shallow' treaty.
Keywords: 330; Klimaschutz; Umweltabkommen; Internationale Umweltpolitik; Pareto-Optimum; Spieltheorie